EFEKTIVITAS PENYALURAN BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) KEPADA MASYARAKAT TERDAMPAK COVID-19 DI DESA KEPATIHAN KABUPATEN JOMBANG - Winona Islamay Firmansyah; Eva Hany Fanida (Publika, 2022)
The Covid-19 pandemic is a new problem that is being faced all over the world. Indonesia is one of the countries that is struggling against the impact of the pandemic which has affected the country's economic sector. The government has taken steps to refocus the village fund budget, including in establishing the Village Fund Direct Assistance (BLT-DD) program to deal with poverty problems caused by the Covid-19 pandemic. However, in the implementation of this program, there are still many problems such as data collection problems, double assistance, not on target and so on. This study was conducted to describe the effectiveness of the BLT-DD program carried out in Kepatihan Village, Jombang Regency. Collecting data in this study in the form of interviews, observations, literacy studies and documentation. The data analysis technique is carried out by the process of collecting data, reducing data, presenting data and drawing conclusions. This study assessed using eight indicators of effectiveness of the program is the precision of the timing, cost calculation, measurement, identify options, precision in thinking, accuracy in performing the command, set goals and target accuracy. Of the eight indicators of program effectiveness, there are four indicators that show less than optimal results, namely the indicators of timeliness, accuracy of choice, accuracy in measurement and accuracy of targets. The gap that occurs between the standards set and their implementation results in unsatisfactory results. Inharmonious policies that underlie the BLT program can be used as evaluation material for the central government and for village governments it is hoped that they will be more selective in selecting prospective beneficiaries. Keywords: Effectiveness, Direct Cash Assistance (BLT), Village Fund